Pengaruh Model Cooperative Learning Tipe Numbered Head Together (NHT) dengan Metode Tutor Sebaya (Peer Tutoring) Terhadap Peningkatan Hasil Belajar Siswa Kelas X MAN 4 Bantul pada Materi Momentum, Impuls dan Tumbukan - Mei Nur Cahyati; Ika Kartika (Jurnal Penelitian Pembelajaran Fisika, 2019)
This research is aimed to know: (1) the effect of Model NHT with Peer Tutoring Method toward the increasing of student’s learning achievement in kognitive aspect (2) the effect of  ModelNHT with Peer Tutoring Method toward the increasing of student’s learning achievement in affective aspect. The research method that be used is quasi experiment with nonequivalent control group design. The population in this research is all of students at Science tenth grade in MAN 4 Bantul academic year 2016/2017. The sample was chosen by surfeited sampling technique that X Science 1 as experiment class and X Science 2 as control class. The results of this research show that (1) Learning with NHT model with peer tutoring gives influence toward the increasing of student’s cognitive learning achievement with N-Gain value 0,52 (medium) within high significance (Effect Size 1,26). The average of student’s kognitive skill on learning with NHT with peer tutoring method get score at 68,57 and with expository learning get score 51,57 (2) Learning with NHT model with peer tutoring gives influence for increasing affective learning achievement with percentage of affective learning achievement at 52,29 % (first meeting), 59,58% (second meeting), and 58,54 % (third meeting), while in the control class gets percentage at 51,61% (first meeting), 52,42% (second meeting), and 52,22 % (third meeting).